Pemberdayaan Siswa SMA melalui Pelatihan Pemasaran Digital di Era Industri 4.0 di Sidoarjo - Edi Widodo; Mulyadi Mulyadi; Rahmat Firdaus (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
Mastery of design technology and digital marketing is a crucial skill in the era of Industry 4.0. These competencies are especially important for the younger generation to support product development and foster entrepreneurial mindsets. This community engagement program aimed to provide training on digital marketing strategies to senior high school and vocational school students in Sidoarjo Regency. Three schools actively participated in the program: SMK Muhammadiyah 3 Ngoro, SMK Trisakti Sidoarjo, and SMK Krian. The activities included the provision of training modules, program socialization, intensive training sessions, and continued mentoring. The training materials focused on content planning, utilization of social media, business account management, and digital promotion strategies tailored to student-created products. The results of the program indicated an increased understanding among participants of both the concepts and practices of digital marketing, as well as the emergence of student-led initiatives to build school-based brands and digital promotional accounts.